Rapid Decarbonization Roadmap for India Based on Photovoltaic Systems - Om Shankar Dev; Ilija Batas Bjelic; Rhythm Singh (Energija, Ekonomija, Ekologija)
According to the Paris Agreement signed by national leaders, the rapid decarbonization roadmap is critical for many citizens worldwide. The burden of saving the climate at acceptable levels urges national energy planning activities accordingly. Currently, India has a fossil fuel dominated power system with a rapid increase in renewable energy installations, namely photovoltaic, in the amount of 10 GW per year. India aims to reach 500 GW of installed electricity capacity from non-fossil fuel sources by 2030. This is a very ambitious target, which would require appropriate planning studies for judicious integration and optimal management of the system. Using Energy PLAN (advanced energy system analysis computer model), the authors created various scenarios involving the integration of the above-mentioned renewable energy based capacities into India’s power system. It will provide key insights into the effects of certain policies and scenarios on the future overall energy balance, as well as the environmental (namely CO2 emissions) and social impact, thus enabling more effective policymaking in this key dimension.